1989
DOI: 10.1007/bf00706958
|View full text |Cite
|
Sign up to set email alerts
|

Childhood victimization: Desensitization effects in the later lifespan

Abstract: The hypothesis tested in this study was that young adults who report having been abused by parents or guardians as children would report less concern when confronted with hypothetical situations similar to the type of abuse they had reportedly experienced during childhood. In our study of nonclinical adults those who reported childhood victimization experiences showed diminished concern toward the specific kind of abuse situation encountered earlier in their lifespan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
2
7
0
Order By: Relevance
“…Even with knowledge about victimization, participants who increasingly adhered to prostitution myths continued to blame the prostituted youth for her circumstances. These findings also support conclusions by Ginsburg et al (1989) and Muller et al (1993) where subjects with physical abuse histories reported increased levels of blame directed toward similar victims (Ginsburg et al, 1989; Muller et al, 1993). It may also be that observers with experiences of childhood physical abuse viewed themselves as too dissimilar from the prostituted youth depicted in the vignette, and thus attributed increased levels of blameworthiness to her, even though she too experienced significant abuse in her family-of-origin.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Even with knowledge about victimization, participants who increasingly adhered to prostitution myths continued to blame the prostituted youth for her circumstances. These findings also support conclusions by Ginsburg et al (1989) and Muller et al (1993) where subjects with physical abuse histories reported increased levels of blame directed toward similar victims (Ginsburg et al, 1989; Muller et al, 1993). It may also be that observers with experiences of childhood physical abuse viewed themselves as too dissimilar from the prostituted youth depicted in the vignette, and thus attributed increased levels of blameworthiness to her, even though she too experienced significant abuse in her family-of-origin.…”
Section: Discussionsupporting
confidence: 87%
“…Thus, questions remain as to whether observers with physical abuse histories would blame prostituted youth for their circumstances. Two analyses have examined the relationship between observer childhood physical abuse and subsequent blame toward physical abuse victims (Ginsburg, Wright, Harrell, & Hill, 1989; Muller, Caldwell, & Hunter, 1993). Individuals with greater perceived similarity to child abuse victims were more likely to blame children for their abuse (Muller et al, 1993).…”
Section: Predictors Of Victim Culpability Assessmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, victims of childhood sexual abuse report less sympathy for physical and sexual abuse victims, as individuals who were sexually victimized in childhood were more likely to also be physically victimized (Franklin & Menaker, 2014;Ginsburg, Wright, Harrell & Hill, 1989). …”
Section: Assessing Rape Myths and Its Correlatesmentioning
confidence: 99%
“…indicates that victims of childhood sexual abuse report less sympathy for sexual abuse victims and, thus, may perceive sex workers more through an offender-orientation (Franklin & Menaker, 2014;Ginsburg et al, 1989). …”
Section: Full Modelsmentioning
confidence: 99%